Why is it so hard to consider personal qualities when selecting medical students?. (2nd April 2020) - Powis, David; Munro, Don; Bore, Miles; Eley, Diann
Abstract: Having 'good' doctors is important to everybody. How to select medical students better has been discussed repeatedly for more than seventy years, implying that prevailing methods could be improved. A significant body of research exists about selection methods and their application in medicine. Yet most medical schools world-wide continue to use prior academic performance and cognitive ability as their major criteria for selection, with minor or no consideration of personal qualities and interpersonal skills (possibly assuming they will develop naturally during training and practice). We describe the main methods available for assessing personal qualities of applicants to medical school and have attempted to identify some reasons and systemic disincentives working against their adoption.